Answer:
H=-12
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
h/6-1=-3
1/6h+-1=-3
1/6h-1=-3
Step 2: Add 1 to both sides.
1/6h+1=-3+1
1/6h=-2
Step 3: Multiply both sides by 6.
6*(1/6h)=6*(-2)
H=-12
Hope this helps
Answer:
Yes
Step-by-step explanation:
6(-1-4)-30(-1) can be simplified into 6(-5)+30 which becomes -30+30, and then 0.
Wat does the picture look like? If you explain a little more, I can give u an answer
<u>Answer</u>:
<em>I'm bad at explaining this but after this, go to sleepppp</em>
<u>Step-by-step explanation:</u>
<u />